Keadilan Distributif atas Pembagian Harta Bersama dalam Perkawinan bagi Keluarga Muslim di Indonesia - Siah Khosyi'ah (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
The division of marital joint property after the breakup of marriage, whether dropping out of marriage due to divorce or due to death, is a new thing in Islamic jurisprudence (fiqh). This is because the concept of mutual treasure is not known in the books of classical Islamic jurisprudence of Muslim scholars of the schools at their times, in which their work are always made as referral in the legal cases up to the present days. In Indonesia, the distribution of common property is regulated in the Compilation of Islamic Laws Articles 96 and 97, which stipulate the rules of distribution of joint property for married couples whose married are off as a result of divorce or death. Article 97 of the Compilation of Islamic Law actually provides an overview of the flexibility of the distribution of common marital property, including in certain cases because the article is regulating (regelen) rather than forcing (dwigen), so that the division is not absolutely divided equally between husband and wife, and casuistically the provisions of that article may be disregarded.